2012
DOI: 10.2319/031512-224.1
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for accelerating orthodontic tooth movement

Abstract: Objective: To evaluate the effectiveness of interventions on accelerating orthodontic tooth movement. Materials and Methods: We searched the databases of PubMed, Embase, Science Citation Index, CENTRAL, and SIGLE from January 1990 to August 2011 for randomized or quasirandomized controlled trials that assessed the effectiveness of interventions on accelerating orthodontic tooth movement. The processes of study search, selection, and quality assessment were conducted independently in duplicate by two review aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
17

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(162 citation statements)
references
References 27 publications
(56 reference statements)
1
144
0
17
Order By: Relevance
“…The majority of published research outcomes indicate an increase in the rate of tooth movement after laser therapy compared to controls; however, there are other reports show no difference after laser application, while other investigations concludes that lasers negatively affect tooth velocity, so according to these findings the effect of low level laser on accelerating orthodontic tooth movement is a contra versial subject (4) .…”
Section: Lilt Canine Retraction Accelerated Tooth Movementmentioning
confidence: 95%
“…The majority of published research outcomes indicate an increase in the rate of tooth movement after laser therapy compared to controls; however, there are other reports show no difference after laser application, while other investigations concludes that lasers negatively affect tooth velocity, so according to these findings the effect of low level laser on accelerating orthodontic tooth movement is a contra versial subject (4) .…”
Section: Lilt Canine Retraction Accelerated Tooth Movementmentioning
confidence: 95%
“…Past notable attempts to shorten orthodontic treatment time included Corticotomy Assisted Orthodontics (CAO) (Gantes, Rathbun & Anholm, 1990;Chung, Oh & Ko, 2001;Wilcko, Wilcko, Bouquot & Ferguson, 2001;Long, Pyakurel, Wang, Liao, Zhou & Lai, 2013) which is based on the principle of Regional Acceleratory Phenomenon, a term first coined by Frost (1981). Physiologically, this theory proposes that when the bone is decorticated, an exuberant bone remodelling phase occurs in which teeth can be rapidly moved through demineralized bone due to an enhancement in cell-mediated tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several innovative modalities have been reported to accelerate orthodontic tooth movement, including low-level laser therapy, pulsed electromagnetic fields, electrical currents, corticotomy, distraction osteogenesis, and mechanical vibration. Recently Long et al (2013) conducted a critical systematic review of randomized controlled trials to assess the effectiveness of these interventions where in they concluded that both corticotomy and distraction were effective and safe to accelerate orthodontic tooth movement. Kharkhar et al (2010) in their quasirandomized controlled trial to evaluate the best approach to reduce the overall orthodontic treatment time by means of distraction osteogenesis inferred that dentoalveolar distraction was superior to periodontal distraction in all areas of assessment.…”
Section: Distraction Device Classificationmentioning
confidence: 99%
“…In an endeavor to elucidate which of the methods would be effective and safe for accelerating orthodontic movement, Chinese researchers developed a systematic review. 5 The authors concluded that low level laser therapy is safe, but incapable of accelerating orthodontic movement, whereas corticotomy is safe and capable of accelerating tooth movement. The other methods need further well designed studies in order to confirm their results.…”
Section: Acceleration Of Tooth Movement Is It Possible?mentioning
confidence: 99%